The Concept of Privacy and Protection of its Inviolability in the Criminal Policy of the Kazakhstan Republic - SHEGEBAYEVA, Aigerim R. (Journal of Advanced Research in Law and Economics, 2016)
The presented article deals with the issues related to the implementation of the criminal policy of the Kazakhstan Republic concerning the privacy of a person. Ensuring the right of privacy of criminal law means provides a solution to such issues as the definition of the private life of a person, a legal restriction or interference in the private (personal) life of man, the criminalization of illegal collection or dissemination of information about the private life of a person and sentence guilty of the correct qualification of the offense. The author studies the concept of privacy, the history of its development, its theoretical rationale, the legislation of the Kazakhstan Republic, which regulates its protection, the opinions of researchers on the imperfection of legal norms. The author draws the conclusion of insufficient legislative development of the concept of privacy required for improving the structure of the Art. 147 of the Criminal Code of the Kazakhstan Republic, recognizes the disbalance between the right to privacy of an individual and the information interests of the society, suggests the solutions to these problems. The absence of a specific law on the protection of privacy, according to the author, cannot effectively protect the right of every person to respect for his private life.
Keywords: privacy, criminal policy, criminal liability, fundamental rights